Dominasi Algoritma Digital terhadap Akal Sehat: Tinjauan Perspektif Al-Qur’an, Hadis, dan Psikologi Islam - Parjana, Cepi (Lembaga Pengkajian Pengembangan Pendidikan dan Kewirausahaan, 2025)
The digital era has fundamentally transformed the information landscape, creating new challenges for individuals in discerning truth and maintaining mental well-being. This article examines the phenomenon of social media algorithm dominance and its impact on human sanity, which, from an Islamic perspective, can be linked to the concept of ghaflah (heedlessness). Drawing upon the Qur'an and Hadith, alongside an integration of views from Islamic and Western psychology, this article emphasizes the urgency of returning to revelation as the primary guide. In-depth analyses of tabayyun (verification), the role of 'aql (intellect) in the light of revelation, and the distinction between hedonic pleasure (instant gratification) versus eudaimonic well-being (meaningful happiness) are presented to reinforce the argument that revelation is the main source of awareness and spiritual health amidst the tumult of digital information.